The Instagram Image of the City. Insights from Lodz, Poland - Zasina Jakub (Bulletin of Geography. Socio-Economic Series, 2018)
The age of big data opens new opportunities for urban research. As millions of users have been creating and transmitting visual representations of cityscapes (e.g., photos taken with smartphones), it is crucial to understand features of the online crowd-sourced images of cities and their relations with their offine archetypes. However, it seems that photos posted by users of social networking sites remain understudied and their informative potential has not been fully exploited yet. The aim of the conducted research was to examine and comprehend the nature of the Instagram image of the city. The paper presents the results of investigating 1867 Instagram photos featuring outdoor city views taken in Lodz, Poland in September 2015. The posted photos were classified by their components and attributes. The study revealed that Instagram content does not reflect the urban space in general. It rather selects geographies and subjects presenting aestheticized and picturesque places and objects. Nevertheless, the new components of cityscapes seem to be noteworthy for Instagram users. Finally, the paper argues that mapping Instagram content without prior and careful examination of the local context may lead to biased conclusions.